Effect of information quality due accounting regulatory changes: Applied case to Mexican real sector - Garza Sánchez, Héctor Horacio; Cortez Alejandro, Klender Aimer; Méndez Sáenz, Alma Berenice; Rodríguez García, Martha del Pilar (Universidad Nacional Autónoma de México, Facultad de Contaduría y Administración, 2017)
Abstract Thepurposeofthispaperistoexaminewhetherchangesinaccountingstandardsimprovevaluerelevance ofﬁnancialinformationonlistedcompaniesinMexico.Theresearchwasconductedfortheperiod2000–2013 usingasampleof141companiesthatreporttotheMexicanstockexchangeusingthemethodologyofpanel data. Our ﬁndings show that changes in local regulations (generally accepted accounting principles) to internationally approved standards (Financial Reporting Standards and International Financial Reporting Standards) increase the value relevance and therefore the quality of information. The study shows that the accounting information with international Financial Reporting Standards is more trustworthy for foreign and national investors. © 2017 Universidad Nacional Autónoma de México, Facultad de Contaduría y Administración. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Keywords: Quality of accounting information; Financial Reporting Standards; International Financial Reporting Standards; Accounting principles